The anisotropic part of a quadratic form over a number field. (March 2023) - Koprowski, Przemysław; Rothkegel, Beata
Abstract: It is well known that every non-degenerate quadratic form admits a decomposition into an orthogonal sum of its anisotropic part and a hyperbolic form. This decomposition is unique up to isometry. In this paper we present an algorithm for constructing an anisotropic part of a given form with coefficients in an arbitrary number field.